Concise synthesis of chiral pyrazolo[4, 3‐f] [1, 4]oxazepines and pyrazolo[4, 3‐f] [1, 4]thiazepines bearing pyrazole unit. (10th December 2020) - Pitchai, Manivel; Ulaganathan, Sankar; Venkateshappa, Suresh Shagathur; Akunuri, Arun; Rampulla, Richard; Mathur, Arvind; Gupta, Anuradha
Abstract: An efficient synthesis of pyrazolo [1, 4]‐oxazepines and [1, 4]‐thiazepines bearing a variety of alkyl and aryl groups with a chiral center has been developed. The synthesis started with readily available 5‐chloro‐pyrazole‐4‐carbaldehyde and chiral amino alcohols. The key step involves intramolecular imine formation. These classes of compounds are potentially useful as templates for drug discovery. Abstract :